Scope and Limitations of TBA[Fe]‐Catalyzed Carbene Transfer to X−H‐bonds – Indication of a Mechanistic Dichotomy. Issue 21 (25th April 2019) - Röske, Annika; Alt, Isabel; Plietker, Bernd
Abstract: An in‐depth study of carbene transfer reactions into polar X−H‐bonds catalyzed by the nucleophilic Fe‐complex Bu4 N[Fe(CO)3 (NO)] (TBA[Fe]) is presented. Whereas alcohols are unreactive, thiols and secondary amines are reactive, silanes showed modest activities. Hammett correlations indicate the presence of an X−H‐acidity dependent mechanistic dichotomy. Abstract : One way or another : The nucleophilic catalyst Bu4 N[Fe(CO)3 (NO)] (TBA[Fe]) catalyzes the insertion of carbenoid reagents into S−H, N−H− and Si−H bonds with good to excellent yields. Hammett‐correlations indicate a mechanistic dichotomy to be present, a probable mechanistic scenario is reported.